1989
DOI: 10.1111/j.1151-2916.1989.tb06221.x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Titanium Carbide Ceramics by High‐Pressure Self‐Combustion Sintering of Titanium Powder and Carbon Fiber

Abstract: Titanium carbide ceramics have been fabricated from the reactants titanium powder and carbon fiber by the highpressure self-combustion sintering method (HPCS) under two pressure conditions (65 MPa and 3 GPa). Porous Tic with a density of about 50% of theoretical was obtained under a pressure of 65 MPa. A possible model accounting for the formation mechanism of Tic is proposed on the basis of observation of the microstructure of the products formed from the incomplete reaction. On the other hand, dense Tic (>95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Adach et al, 6) on the other hand, obtained an appreciable amount of free carbon for the C/Ti ratio equaling 0.8 and 1.05 when the carbon fiber (7 μm in diameter and 0.2 mm in length) was used as the carbon source. As indicated, inconsistency exists in the previous studies regarding the dependence of the stoichiometry of TiCx on the reactant C/Ti ratio and moreover, the nature behind the apparent depending behavior has not yet been disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…Adach et al, 6) on the other hand, obtained an appreciable amount of free carbon for the C/Ti ratio equaling 0.8 and 1.05 when the carbon fiber (7 μm in diameter and 0.2 mm in length) was used as the carbon source. As indicated, inconsistency exists in the previous studies regarding the dependence of the stoichiometry of TiCx on the reactant C/Ti ratio and moreover, the nature behind the apparent depending behavior has not yet been disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, TiC has a good hardness and a very high melting point [5]. Composite materials consisting of TiC and titanium aluminides are expected to find use in various structural, cutting tool and armor applications [6].…”
Section: Introductionmentioning
confidence: 99%
“…TiC ceramics is a sintered material formed by combustion synthesis method from titanium and carbon powder (Ti:C=1:1) at 3000 • C [19]. It was found that the material was porous by the SEM measurement ( Fig.…”
Section: Tic Ceramicsmentioning
confidence: 99%
“…Our research group developed porous titanium carbide (TiC) ceramics [19]. The ceramics has been fabricated from the reactants of titanium powder and carbon fiber by the combustion synthesis method.…”
Section: Introductionmentioning
confidence: 99%